Survey of LEU olympiad 2013 for young mathematicians - Jakaitytė, Eglė; Kaučikas, Algirdas; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2013)
The texts and solutions of the LEU young mathematicians olympiad – 2013 are presented.